Altered chemotactic response to CXCL12 in patients carrying GATA2 mutations. Issue 6 (28th December 2015) - Maciejewski‐Duval, Anna; Meuris, Floriane; Bignon, Alexandre; Aknin, Marie‐Laure; Balabanian, Karl; Faivre, Laurence; Pasquet, Marlène; Barlogis, Vincent; Fieschi, Claire; Bellanné‐Chantelot, Christine; Donadieu, Jean; Schlecht‐Louf, Géraldine; et al.
Abstract : Specific impairment of expression and chemotactic function of CXCR4 in NK cells from patients with GATA2 deficiency. Abstract : GATA2 deficiency—formerly described as MonoMAC syndrome; dendritic cells, monocytes, B cells, and natural killer cell deficiency; familial myelodysplastic syndrome/acute myeloid leukemia; or Emberger syndrome—encompasses a range of hematologic and nonhematologic anomalies, mainly characterized by monocytopenia, B lymphopenia, natural killer cell cytopenia, neutropenia, immunodeficiency, and a high risk of developing acute myeloid leukemia. Herein, we present 7 patients with GATA2 deficiency recruited into the French Severe Chronic Neutropenia Registry, which enrolls patients with all kinds of congenital neutropenia. We performed extended immunophenotyping of their whole blood lymphocyte populations, together with the analysis of their chemotactic responses. Lymphopenia was recorded for B and CD4 + T cells in 6 patients. Although only 3 patients displayed natural killer cell cytopenia, the CD56 bright natural killer subpopulation was nearly absent in all 7 patients. Natural killer cells from 6 patients showed decreased CXCL12/CXCR4‐dependent chemotaxis, whereas other lymphocytes, and most significantly B lymphocytes, displayed enhanced CXCL12‐induced chemotaxis compared with healthy volunteers. Surface expression of CXCR4 was significantly diminished in the patients' natural killer cells, although the total expression of the receptor was found to be equivalent to that of natural killer cells from healthy individual controls. Together, these data reveal that GATA2 deficiency is associated with impaired membrane expression and chemotactic dysfunctions of CXCR4. These dysfunctions may contribute to the physiopathology of this deficiency by affecting the normal distribution of lymphocytes and thus potentially affecting the susceptibility of patients to associated infections.